Irrigation with commercial bottled water increases generation of reactive oxygen species in Nicotiana tabacum. Issue 1 (1st January 2020) - Calderón-Torres, Marissa; López-Estrada, Edith; Ortiz-Reyes, Ana E.; Murguía-Romero, Miguel
ABSTRACT: The consumption of commercial bottled water worldwide has increased surprisingly. To ensure that its consumption has no harmful effects on human health, research must be carried out with living organisms. The growth of Nicotiana tabacum plants was analyzed after being irrigated with tap and commercial bottled water. Plants irrigated with commercial bottled water had leaves with chlorosis, smaller number of leaves with a shorter length of stem and leaf, compared to plants irrigated with tap water, and root, stem and leaf showed an increase of reactive oxygen species production with a significant decrease of chlorophylls. Chemical analysis of commercial bottled water showed a low ion concentration, and an acidic pH value (5.5) which is below the minimum of Mexican NOM-127-SSA1-2000 pH value standard (6.5–8.5). The growth, chlorophyll concentration and antioxidant capacity of plants irrigated with bottled water are negatively affected compared to those irrigated with tap water. Graphical abstract: uf0001